An improved urine collection pad method: a randomised clinical trial. Issue 8 (21st July 2004) - Rao, S; Bhatt, J; Houghton, C; Macfarlane, Peter
Abstract : Aim: To evaluate a modified urine collection pad (UCP) method for its ability to reduce heavy mixed growth bacterial contamination of UCP samples in young children with suspected urinary tract infection (UTI). Method: Febrile children under 2 years of age were randomised to two UCP methods: the same UCP kept in the nappy until urine was passed (single UCP group), or the UCP replaced with a fresh one every 30 minutes until urine was passed (replaced UCP group). In both groups a moisture sensitive audio alarm was used to signal passage of urine. Results: Eighty children were enrolled and a satisfactory sample was obtained in 68 (37 in the single UCP group and 31 in the replaced UCP group). In 12 children (15%), collection failed, mainly because of faecal soiling of the pad. UTI occurred in three children (4%). In the remaining 65 samples, heavy mixed growth (> 10 5 organisms/ml) occurred in 1/31 (3%) in the replaced UCP group compared with 10/35 (29%) in the single UCP group (p = 0.008). There were no adverse effects from the use of the moisture sensitive audio alarm. Conclusion: Changing the UCP every 30 minutes almost eliminates heavy mixed growth contamination of UCP samples and substantially increases the proportion of UCP results that confidently exclude UTI. This represents a simple and clinically important improvement to the UCP method which is reliable for diagnosing and excluding UTI in young children still in nappies. It has potential for use in outpatient clinics, in the primary healthcare setting, or at home.